Pengaruh ekstrak kemangi (Ocimum basilicum forma citratum) terhadap perkembangan lalat rumah (Musca domestica) (L.) - Dattu Iffah H; Dwi Jayanti Gunandini; Agus Kardinan (Jurnal Entomologi Indonesia, 2008)
Effect of Kemangi Extract (Ocimum basilicum forma citratum) to House Fly (Musca domestica) (L.). The aim of this study was to know larvacidal effect of basil leave on house fly (Musca domestica ). Using atsiri oil which extracted through the steam distillation procedure, this study applied 5 treatments and 4 replications. The treatment were 2.5, 5, 10, and 20% asitri oil dilluted on water compared to control (water only, 0%), The study showed that 20% dilluotion has highest larvacidal effect, cause highest mortality rate (83%), and inhibited ecdysis shown by lowest ecdysis and enclosy ability sharing only 13 and 37%.